Restoration of Victims’ Rights in the Perspective of Law and Development - Fahrizal S.Siagian; Mahmud Mulyadi (Jurnal Restorasi : Hukum dan Politik, 2025)
Crime as a classical problem has always accompanied human life. Crime gives rise to victims who suffer physical, mental, and/or economic losses as a result of criminal acts. The global shift in the criminal justice process—from a retributive to a restorative approach—indicates a significant development. Therefore, a study is needed to examine how the restoration of victims’ rights can be viewed from the perspective of law and development. The purpose of this research is to address this issue. This study employs a normative juridical method using a library research approach. The findings reveal that crime continues to develop significantly, requiring criminal law to adapt and accommodate these changes by reforming existing mechanisms within the criminal justice system. The evolution of criminal justice processes that now recognize and guarantee victims’ rights to recovery represents an absolute and mandatory obligation. Furthermore, the restoration of victims’ rights should be implemented automatically, without requiring a formal request to the state to provide protection for every victim. This automatic recognition constitutes the novelty of this research.